Preparation method of nanofiltration membrane

By combining mesoporous nano-silica and amino-β-cyclodextrin derivatives with zwitterionic compounds, the pore size and water flux of nanofiltration membranes are optimized, solving the problems of insufficient water flux and poor separation effect of existing nanofiltration membranes. This achieves efficient separation of ions with different valence states and stable water flux, making it suitable for large-scale production.

CN121016513AActive Publication Date: 2025-11-28SHANDONG ZHAOJIN MOTIAN

Patent Information

Application Number
CN202511562692.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2025-11-28
Estimated Expiration
2045-10-30

AI Technical Summary

Technical Problem

Existing nanofiltration membranes suffer from insufficient water flux and unsatisfactory separation effect when separating ions of different valence states. Furthermore, they have low production efficiency and high costs, which are not conducive to large-scale production.

Method used

Mesoporous nano-silica and amino-β-cyclodextrin derivatives are used as anchoring agents, combined with zwitterionic compounds and co-solvents, to form a stable hydration region and electric double layer on the surface of nanofiltration membrane through a composite structure, thereby enhancing the donan repulsion effect and optimizing pore size uniformity and water flux.

Benefits of technology

It improves the water flux and separation capability of nanofiltration membranes for ions of different valence states, has good stability, controllable cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121016513A_ABST
    Figure CN121016513A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of semipermeable membrane preparation, and particularly relates to a preparation method of a nanofiltration membrane. The preparation method comprises the following steps: (1) cleaning the supporting layer for later use; the preparation method comprises the following steps: blending diamine, an amino beta-cyclodextrin derivative, an inorganic hybridizing agent, a zwitterionic compound and water to obtain a water phase for later use; blending aromatic acyl chloride, a cosolvent and an organic solvent to obtain an oil phase for later use; and (2) sequentially carrying out primary impregnation in a water phase, membrane scraping, secondary impregnation in an oil phase and heating curing on the supporting layer, and finally carrying out post-treatment to obtain the nanofiltration membrane. The nanofiltration membrane is prepared by introducing the amino beta-cyclodextrin derivative, the inorganic hybridization agent and other components into polyamide, so that the water flux of the polyamide nanofiltration membrane and the capability of effectively separating ions with different valence states are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of semi-permeable membrane preparation, and particularly relates to a preparation method of a nanofiltration membrane. BACKGROUND

[0002] The nanofiltration membrane, abbreviated as NF, can be used for intercepting small organic molecules and high-valence ions by means of pore size screening and charge repulsion, and can obtain clean water containing low-valence ions, and has the advantages of large yield, low energy consumption and high separation efficiency. At present, the nanofiltration membrane product is generally a multi-layer composite structure, including a non-woven fabric base layer, a support layer and a separation layer, and the separation layer is made of polyamide material. Since the surface charge density and distribution of the polyamide material are difficult to accurately control, the Donnan effect based on charge repulsion has limited separation capacity for different valence ions, which often manifests as that the separation degree of the nanofiltration membrane for different valence ions is not ideal, or the water flux is sacrificed to achieve high interception rate for high valence ions. Therefore, it is urgent to develop a nanofiltration membrane with large water flux and effective separation capacity for different valence ions.

[0003] Chinese patent CN102872726A discloses a preparation method of a Ti-Zr composite nanofiltration membrane, which is composed of synthesis of Ti-Zr composite sol, film coating and drying sintering. The synthesis of the Ti-Zr composite sol is that a zirconium precursor, a titanium precursor and a solvent are uniformly mixed in proportion, then a chelating agent is added and uniformly mixed, then water is added for dilution in an ice bath, and finally a constant temperature water bath is used for reaction. The zirconium precursor is one of zirconium oxychloride, zirconium n-propyl alcohol or zirconium n-butyl alcohol; the titanium precursor is one of titanium ethoxide, titanium isopropoxide or titanium tert-butoxide; and the drying sintering is that the carrier coated with the membrane preparation liquid is dried, heated to 300-600℃ at a rate of 0.2-2℃ / min, and then naturally cooled after being kept warm for 1-10h.

[0004] The patent uses zirconium and titanium organic metal precursors as raw materials to prepare Ti-Zr composite sol as a membrane matrix, and further needs to coat the Ti-Zr composite sol on a γ-Al2O3 membrane, a ZrO2 membrane or a TiO2 membrane carrier, and slowly heat and sinter to form a shape. These raw material selection and operation directly lead to low production efficiency and high cost of the nanofiltration membrane, which is not conducive to the application in large-scale production scenarios. SUMMARY

[0005] The purpose of the present application is to provide a preparation method of a nanofiltration membrane, and further improve the water flux of the polyamide nanofiltration membrane and the separation capacity for different valence ions.

[0006] To achieve the above purpose, the technical solution adopted by the present application is as follows: The preparation method of the nanofiltration membrane comprises the following steps: (1) The support layer is cleaned for standby; the binary amine, amino β-cyclodextrin derivative, inorganic hybrid agent, and amphoteric ionic compound are blended with water to obtain an aqueous phase for standby; the aromatic acyl chloride, cosolvent, and organic solvent are blended to obtain an oil phase for standby; (2) The support layer is sequentially immersed in the aqueous phase, scraped, immersed in the oil phase again, and cured by heating, and finally post-treated to obtain a nanofiltration membrane.

[0007] Among them: The support layer is one of polysulfone, polyether ketone, or polyether sulfone, and the thickness of the support layer is 45-70 μm; during cleaning, the support layer is sequentially placed in a cleaning solution and acidic water for ultrasonic cleaning.

[0008] The cleaning solution is prepared according to a mass ratio of isomeric fatty alcohol polyoxyethylene ether to water of 1:(40-70), the mass ratio of the support layer to the cleaning solution is 1:(10-13), the mass ratio of the support layer to the acidic water is 1:(13-15), and the pH of the acidic water is 4.2-5.0; during ultrasonic cleaning in the cleaning solution, the ultrasonic power is 180-220 W and the ultrasonic time is 6-10 min; during ultrasonic cleaning in the acidic water, the ultrasonic power is 180-220 W and the ultrasonic time is 2-4 min. The isomeric fatty alcohol polyoxyethylene ether is one of TO-8, TO-10, or XL-90.

[0009] In step (1), the binary amine is piperazine, the amino β-cyclodextrin derivative is mono-(6-ethylenediamino-6-deoxy)-β-cyclodextrin or mono-(6-amino-6-deoxy)-β-cyclodextrin, the inorganic hybrid agent is mesoporous nanosilica, the specification of the mesoporous nanosilica is a pore size of 7.8 nm and an average particle size of 200 nm, and the amphoteric ionic compound is 1-butylsulfonic acid-3-methyl imidazole chloride.

[0010] In step (1), the aromatic acyl chloride is trimesoyl chloride, the cosolvent is tributyl phosphate, and the organic solvent is one of n-hexane, tetrahydrofuran, or cyclohexane.

[0011] In step (1), the mass ratio of the binary amine, amino β-cyclodextrin derivative, inorganic hybrid agent, and amphoteric ionic compound to water is (3-4):(1.4-1.8):(1.65-2):(2-4):(42-46), and the mass ratio of the aromatic acyl chloride, cosolvent, and organic solvent is 5:(1.9-3):(36-48).

[0012] The first immersion temperature is 26-35℃, and the first immersion time is 120-180 s; the second immersion temperature is 25-32℃, the second immersion time is 50-90 s, and after the second immersion is completed, the support layer is placed for 8-20 min until no liquid drops are observed within 60 s of vertical dripping.

[0013] The mass ratio of the support layer, the diamine and the aromatic acid chloride in the first and second impregnation is 500:5:(3~4):5.

[0014] The line pressure in the film scraping is 0.38~0.60 bar, the film scraping rate is 15~25 cm / s, the film scraping temperature is 15~30℃, and the film scraping is completed until no drop flows within 60 s of vertical dripping.

[0015] The heating and curing temperature is 65~75℃, and the heating and curing time is 4~8 min.

[0016] The beneficial effects of the present application are as follows: The present application uses the mesoporous structure of mesoporous nanosilica and the truncated cone large ring structure of amino beta-cyclodextrin derivative as anchor points to uniformly anchor zwitterionic compounds. This composite structure can form a stable hydration area on the membrane surface with the help of zwitterions. Since the zwitterionic compound has a negatively charged sulfonate and a positively charged imidazole ring, a double electric layer can be spontaneously formed in the hydration area without the need to form a double electric layer by capturing salt ions. The double electric layer in the mesoporous structure can avoid the rapid decline of water flux caused by the formation of a double electric layer on the membrane surface, balance the trade-off effect of the nanofiltration membrane, provide a longer action path for the Donnan exclusion effect, and further separate monovalent ions (sodium chloride, Na + , Cl - ) and divalent ions (magnesium sulfate, Mg 2+ , SO4 2- ), preventing monovalent ions from passing through the nanofiltration membrane with divalent ions.

[0017] The amino beta-cyclodextrin derivative has a truncated cone large ring structure with a hydrophilic outer ring and a hydrophobic inner ring. The amino group on the outer ring can be embedded in the polyamide structure, making the polyamide structure looser and providing more nanoscale water channels for the nanofiltration membrane. The mesoporous nanosilica is surrounded by the large ring structure of the amino beta-cyclodextrin derivative through hydrogen bonding, effectively improving the water flux through the funnel effect. In addition, the mesoporous nanosilica itself has a regular and continuous mesoporous structure, with rigidity and low resistance characteristics, which can ensure the stability of water flux and prevent it from being affected by external conditions.

[0018] The amphoteric ionic compound can be combined with the silicon hydroxyl on the surface of the mesoporous nanosilica, the outer ring hydrophilic group of the amino β-cyclodextrin derivative and the cosolvent through hydrogen bonding by the hydration ability of the amphoteric ionic group of the amphoteric ionic compound, to form a composite hydrophilic interface; the composite hydrophilic interface further improves the retention rate of the divalent ion; in addition, the uniform dispersion of the amino β-cyclodextrin derivative in the polyamide matrix is promoted, and the resistance of water molecules entering the mesopore is further reduced, which, together with the sieving effect of the mesoporous nanosilica, improves the water flux of the membrane.

[0019] The cosolvent (tributyl phosphate) interacts with the mesoporous nanosilica, the amino β-cyclodextrin derivative and the amphoteric ionic compound through the phosphate group, and the macromolecules such as the amino β-cyclodextrin derivative and the composite hydrophilic interface structure can be embedded in the polyamide network by means of the symmetric distribution of the ester chain, so as to optimize the pore size uniformity on the polyamide membrane, macroscopically balance the water flux and the retention rate to a certain extent, and obtain a higher water flux and a better retention rate. At the same time, the cosolvent and the amphoteric ionic compound jointly promote the uniform dispersion of the β-cyclodextrin derivative, which cooperates with the double electric layer to further improve the selectivity of the nanofiltration membrane. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 SEM image of the nanofiltration membrane in Example 1. DETAILED DESCRIPTION

[0021] The application will be described and explained in detail with reference to the following examples.

[0022] Example 1 A cleaning solution was prepared according to the mass ratio of TO-10: pure water = 1:70, 500g, 45μm thick polysulfone membrane was placed in 6500g cleaning solution, and after ultrasonic treatment at 200W for 6.5min, it was taken out and placed in 7000g, pH=4.2 acidic water, and ultrasonic treatment was carried out at 200W for 2min, and then dried for standby. 400g piperazine, 180g mono-(6-ethylenediamine-6-deoxy)-β-cyclodextrin, 180g mesoporous nanosilica (specification: pore size 7.8nm, average particle size 200nm), 260g 1-butyl sulfonic acid-3-methyl imidazole chloride and 4600g water were stirred until a suspension was obtained, to prepare an aqueous phase for standby; 500g trimesoyl chloride, 190g tributyl phosphate and 3600g n-hexane were blended to obtain an oil phase for standby.

[0023] The prepared polysulfone membrane was immersed in the water phase for 180 s at 28 °C, and then taken out. The rubber roller was used to scrape the polysulfone membrane under the conditions of an online pressure of 0.38 bar, a scraping rate of 25 cm / s, and a scraping temperature of 30 °C, to obtain a layer of water phase liquid membrane with uniform thickness. The scraping was completed when there was no dripping within 60 s of vertical dripping. The prepared polysulfone membrane was immersed in the oil phase for 90 s at 32 °C, and then taken out. The membrane was placed for 15 min, and the second immersion was completed when there was no dripping within 60 s of vertical dripping. Subsequently, the membrane was heated at 65 °C for 8 min, taken out, cooled to room temperature, and then immersed in n-hexane and pure water for 20 min, respectively, and vacuum dried to a constant weight to obtain a nanofiltration membrane. The SEM image of the nanofiltration membrane is shown in FIG. 1. Figure 1

[0024] Example 2 The prepared polysulfone membrane was immersed in the water phase for 160 s at 26 °C, and then taken out. The rubber roller was used to scrape the polysulfone membrane under the conditions of an online pressure of 0.42 bar, a scraping rate of 20 cm / s, and a scraping temperature of 25 °C, to obtain a layer of water phase liquid membrane with uniform thickness. The scraping was completed when there was no dripping within 60 s of vertical dripping. The prepared polysulfone membrane was immersed in the oil phase for 60 s at 25 °C, and then taken out. The membrane was placed for 20 min, and the second immersion was completed when there was no dripping within 60 s of vertical dripping. Subsequently, the membrane was heated at 70 °C for 7 min, taken out, cooled to room temperature, and then immersed in cyclohexane and pure water for 25 min, respectively, and vacuum dried to a constant weight to obtain a nanofiltration membrane.

[0025] The prepared polysulfone membrane was immersed in the water phase for 160 s at 26 °C, and then taken out. The rubber roller was used to scrape the polysulfone membrane under the conditions of an online pressure of 0.42 bar, a scraping rate of 20 cm / s, and a scraping temperature of 25 °C, to obtain a layer of water phase liquid membrane with uniform thickness. The scraping was completed when there was no dripping within 60 s of vertical dripping. The prepared polysulfone membrane was immersed in the oil phase for 60 s at 25 °C, and then taken out. The membrane was placed for 20 min, and the second immersion was completed when there was no dripping within 60 s of vertical dripping. Subsequently, the membrane was heated at 70 °C for 7 min, taken out, cooled to room temperature, and then immersed in cyclohexane and pure water for 25 min, respectively, and vacuum dried to a constant weight to obtain a nanofiltration membrane.

[0026] Example 3 ​The cleaning solution was prepared according to the mass ratio of XL-90: pure water = 1:45, 500 g of polyether sulfone film with a thickness of 70 μm was placed in 5500 g of the cleaning solution, and after ultrasonic treatment at 220 W for 6 min, it was taken out and placed in 6800 g of pH = 5.0 acidic water, and after ultrasonic treatment at 220 W for 3.5 min, it was dried for standby. 360 g of piperazine, 150 g of mono-(6-amino-6-deoxy)-β-cyclodextrin, 200 g of mesoporous nanosilica (with a pore size of 7.8 nm and an average particle size of 200 nm), 350 g of 1-butylsulfonic acid-3-methyl imidazole chloride, and 4200 g of water were stirred until a suspension was obtained to prepare an aqueous phase for standby; 500 g of trimesoyl chloride, 280 g of tributyl phosphate, and 3800 g of n-hexane were blended to obtain an oil phase for standby.

[0027] The standby polyether sulfone film was immersed in the aqueous phase for 130 s at 30 °C, and then taken out and passed through a rubber roller in parallel under the conditions of an online pressure of 0.46 bar, a doctor blade speed of 18 cm / s, and a doctor blade temperature of 20 °C to obtain a uniform aqueous phase liquid film, and the doctoring was completed when there was no dripping within 60 s of vertical dripping. The standby polyether sulfone film was immersed in the oil phase for the second time for 70 s at 30 °C, and then taken out and placed for 8 min, and the second immersion was completed when there was no dripping within 60 s of vertical dripping. Subsequently, it was heated at 75 °C for 5 min, taken out, cooled to room temperature, immersed in n-hexane and pure water for 30 min, and then vacuum dried to a constant weight to obtain a nanofiltration membrane.

[0028] Example 4 The cleaning solution was prepared according to the mass ratio of TO-8: pure water = 1:60, 500 g of polyether ketone film with a thickness of 55 μm was placed in 5000 g of the cleaning solution, and after ultrasonic treatment at 180 W for 10 min, it was taken out and placed in 6500 g of pH = 4.3 acidic water, and after ultrasonic treatment at 180 W for 3 min, it was dried for standby. 300 g of piperazine, 140 g of mono-(6-amino-6-deoxy)-β-cyclodextrin, 165 g of mesoporous nanosilica (with a pore size of 7.8 nm and an average particle size of 200 nm), 400 g of 1-butylsulfonic acid-3-methyl imidazole chloride, and 4400 g of water were stirred until a suspension was obtained to prepare an aqueous phase for standby; 500 g of trimesoyl chloride, 200 g of tributyl phosphate, and 4100 g of tetrahydrofuran were blended to obtain an oil phase for standby.

[0029] The polyether ketone membrane was immersed in the water phase for 120 s at 35 °C, and then taken out. The membrane was scraped with a rubber roller under the conditions of an online pressure of 0.60 bar, a scraping rate of 15 cm / s, and a scraping temperature of 15 °C to obtain a uniform water phase liquid film. The scraping was completed when no liquid dripped from the membrane within 60 s of vertical dripping. The polyether ketone membrane was immersed in the oil phase for 50 s at 28 °C, and then taken out. The membrane was placed for 16 min, and the second immersion was completed when no liquid dripped from the membrane within 60 s of vertical dripping. Subsequently, the membrane was heated at 72 °C for 4 min, and then taken out. The membrane was cooled to room temperature, and then immersed in tetrahydrofuran and pure water for 22 min, respectively. The membrane was vacuum dried to a constant weight to obtain a nanofiltration membrane.

[0030] Comparative Example 1 The remaining steps and the raw materials used were the same as in Example 1, except that no amino β-cyclodextrin derivative was added.

[0031] Comparative Example 2 The remaining steps and the raw materials used were the same as in Example 1, except that no mesoporous nano-silicon dioxide was added.

[0032] Comparative Example 3 The remaining steps and the raw materials used were the same as in Example 1, except that no amphoteric compound was added.

[0033] Comparative Example 4 The remaining steps and the raw materials used were the same as in Example 1, except that no cosolvent was added.

[0034] Evaluation of the implementation effect The nanofiltration membranes prepared in Examples 1 to 4 and Comparative Examples 1 to 4 and commercially available nanofiltration membranes were cut to have an effective area of 0.6 m 2 ±0.1 cm 2 The membranes were immersed in pure water at 0.3 MPa and 25 ± 0.2 °C for 20 min for pre-pressing until the water flux was stable, and then the membranes were immersed in pure water for standby use. A test solution containing 5000 mg / L of sodium chloride and 5000 mg / L of magnesium sulfate was prepared for standby use.

[0035] Standard water inlet conditions were set, the pressure was 0.3 ± 0.05 MPa, the temperature was 25 ± 0.2 °C, the test solution was introduced into the nanofiltration membrane, and the volume V0 on the water production side was recorded after 20 min. The initial water flux J0 was calculated. After continuous operation for 220 h, the concentrations of sodium chloride and magnesium sulfate on the water production side and the volume V t were recorded, and the rejection rate and the water flux J t after 220 h were calculated.

[0036] Water flux calculation (J, unit L·m -2 ·h -1 ): Wherein V represents water production volume (unit L) ; A represents effective area of the nanofiltration membrane (m 2 ) ; t represents operation time (h).

[0037] Water flux attenuation rate (Delta J) calculation: Wherein J0 represents initial water flux; J t represents water flux after 220 hours.

[0038] Specific test results are shown in Table 1.

[0039] Table 1 nanofiltration membrane performance test results

[0040] As can be seen from Table 1, compared with Comparative Examples 1-4 and commercially available nanofiltration membranes, the nanofiltration membrane prepared by the application has higher initial water flux and water flux after 220 hours of water inlet, and lower water flux attenuation rate, indicating that the nanofiltration membrane prepared by the application has more stable water production performance in high salt environment; in addition, the magnesium sulfate removal rate of the application examples is greater than 99%, the sodium chloride removal rate is less than 23%, and the nanofiltration membrane has excellent salt separation performance. Finally, the raw materials for preparing the application are easy to obtain, the cost is controllable, the production operation is safe and simple, and it is convenient for large-scale production, and it has good application prospect in the field of salt separation nanofiltration membrane.

Claims

1. A method for preparing a nanofiltration membrane, characterized in that, Includes the following steps: (1) Clean the support layer for later use; mix the diamine, aminoβ-cyclodextrin derivative, inorganic hybrid agent, zwitterionic compound and water to obtain an aqueous phase for later use; mix the aromatic acyl chloride, cosolvent and organic solvent to obtain an oil phase for later use; (2) The support layer is sequentially immersed in the aqueous phase once, scraped, immersed in the oil phase a second time, and heated and cured. Finally, after post-treatment, a nanofiltration membrane is obtained.

2. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (1), the support layer is one of polysulfone, polyetherketone or polyethersulfone, and the thickness of the support layer is 45~70μm; during cleaning, the support layer is placed in the cleaning solution and acidic water in sequence for ultrasonic cleaning.

3. The method for preparing a nanofiltration membrane according to claim 2, characterized in that, In step (1), the cleaning solution is prepared according to the mass ratio of isomeric fatty alcohol polyoxyethylene ether to water of 1:(40~70), the mass ratio of the support layer to the cleaning solution is 1:(10~13), the mass ratio of the support layer to acidic water is 1:(13~15), and the pH of the acidic water is 4.2~5.

0. When ultrasonic cleaning in the cleaning solution, the ultrasonic power is 180~220W and the ultrasonic time is 6~10min. When ultrasonic cleaning in acidic water, the ultrasonic power is 180~220W and the ultrasonic time is 2~4min.

4. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (1), the diamine is piperazine, the aminoβ-cyclodextrin derivative is mono-(6-ethylenediamino-6-deoxy)-β-cyclodextrin or mono-(6-amino-6-deoxy)-β-cyclodextrin, the inorganic hybrid agent is mesoporous nano silica, and the zwitterionic compound is 1-butylsulfonic acid-3-methylimidazolium chloride.

5. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (1), the aromatic acyl chloride is pyromellitic acyl chloride, the co-solvent is tributyl phosphate, and the organic solvent is one of n-hexane, tetrahydrofuran, or cyclohexane.

6. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (1), the mass ratio of diamine, aminoβ-cyclodextrin derivative, inorganic hybrid agent, zwitterionic compound and water is (3~4):(1.4~1.8):(1.65~2):(2~4):(42~46); the mass ratio of aromatic acyl chloride, cosolvent and organic solvent is 5:(1.9~3):(36~48).

7. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (2), the first immersion temperature is 26~35℃ and the first immersion time is 120~180s; the second immersion temperature is 25~32℃ and the second immersion time is 50~90s; after the second immersion, the plant is left to stand for 8~20min.

8. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (2), the mass ratio of the support layer, diamine, and aromatic acyl chloride during the first and second impregnation is 5:(3~4):

5.

9. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (2), the linear pressure during film scraping is 0.38~0.60 bar, the film scraping speed is 15~25 cm / s, and the film scraping temperature is 15~30℃.

10. The method for preparing a nanofiltration membrane according to claim 1, characterized in that, In step (2), the heating curing temperature is 65~75℃ and the heating curing time is 4~8min.

Citation Information

Patent Citations

  • Method for preparing Ti-Zr composite nanofiltration membrane

    CN102872726A

  • A polyamide nanofiltration membrane containing zwitterions and its preparation method

    CN102294178A

  • Mesoporous silica sphere / semi-aromatic polyamide nano-composite reverse osmosis membrane and preparation method thereof

    CN104841295A

  • Composite membrane for water treatment, and preparation method thereof

    CN106345318A

  • Preparation method of high separation performance and very low pressure polyaramid based composite reverse osmosis membrane

    CN109675449A

Cited By

  • Composite nanofiltration membrane, preparation method thereof and water treatment device

    CN121490602A

  • Composite nanofiltration membrane, method for preparing the same, and water treatment device

    CN121490602B